Investigation on friction, antiwear, and extreme pressure properties of different grades of polyalphaolefins with functionalized multi-walled carbon nanotubes as an additive - Kumar, H.; Harsha, A.P. (American Society of Mechanical Engineers (ASME), 2020)
In the present investigation, the COOH-functionalized multi-walled carbon nanotubes (MWCNTs) having an outer diameter of 20-30 nm and length 1−2 μm were dispersed in four different grades of polyalphaolefins (PAOs; i.e., PAO 4, PAO 6, PAO 40, and PAO 100) at various concentrations (0.025, 0.05, 0.075, 0.10, and 0.15 wt%) to evaluate friction, anti-wear, and extreme pressure properties. The tribological test was conducted as per ASTM standard using four-ball tester. The test results showed that with the addition of MWCNTs, the friction and wear properties of PAOs had been improved significantly as compared to the base oils. It was also observed that MWCNTs exhibited excellent anti-wear properties than friction properties. The possible reasons for the improvement in friction and wear properties are discussed with the aid of various analytical tools. Copyright © 2020 by ASME
Keywords: polyalphaolefins (PAOs); multi-walled carbon nanotubes (MWCNTs); friction; lubricant additives; lubricants